Jafarova, Rumella - (:unkn) unknown (My University, 2026)
Rumella Telman Jafarova graduated with distinction from the Azerbaijan University of Architecture and Construction (AzUAC) with a Bachelor’s degree in Economics and Management of Construction in 2006 and a Master’s degree with distinction in the same field in 2008. From 2007 to 2008, she worked as a Leading Economist at the Research Institute of the Ministry of Defence Industry of the Republic of Azerbaijan. In 2014, she successfully defended her PhD dissertation, Development of Entrepreneurial Activity in the Construction Sector of Azerbaijan, and was awarded the degree of Doctor of Philosophy (PhD) in Economics in the specialty 5312.01 – Sectoral Economics. Since 2021, she has been working as a Senior Lecturer at AzUAC, and in 2024 she was awarded the academic title of Associate Professor.